POTENTIAL UTILISATION MAPPING OF STATE-OWNED ASSETS IN THE FORM OF LAND AND BUILDING LEASE IN PALANGKARAYA CITY - Dorojatun, Helvita; Purwanto, Edi (PLANNING MALAYSIA, 2019)
This paper discusses on how the Directorate General of State Assets Management (DGSAM), as the state-owned asset manager, under the Ministry of Finance of the Republic of Indonesia, analyses the best suited strategy to map public assets. The tremendous amount of assets to be managed are scattered all over Indonesian archipelago. As one of the revenue centres for the nation, DGSAM needs to have more information about the feasibility of those assets. This study addresses the mapping of potential state-owned assets and measures the potential revenue to find out how much that can be generated from them. Asset mapping was done using geographical information system analysis, while the potential value of the appraised assets is calculated using artificial neural network. The study takes place in Palangkaraya, the largest city in this country, which might be the promising capital city of Indonesia in the near future. Based on the findings, it is clear that the government assets which can be exploited in Palangkaraya alone are about 14,302 m2 of land with the potential revenue of USD 86,040/year, and 141 rooms which are predicted to generate around USD 106,342/year, with appropriate occupancy rate in the market.